2000
DOI: 10.1093/emboj/19.11.2719
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous targeting of Bacillus subtilis cell division protein DivIVA to division sites in Escherichia coli and fission yeast

Abstract: The Bacillus subtilis divIVA gene encodes a coiledcoil protein that shows weak similarity to eukaryotic tropomyosins. The protein is targeted to the sites of cell division and mature cell poles where, in B.subtilis, it controls the site speci®city of cell division. Although clear homologues of DivIVA are present only in Gram-positive bacteria, and its role in division site selection is not conserved in the Gram-negative bacterium, Escherichia coli, a DivIVA±green¯uores-cent protein (GFP) fusion was targeted ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
99
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 57 publications
(86 reference statements)
13
99
2
Order By: Relevance
“…We should point out, however, that experiments in round cell mutants have indicated that simple curvature of the cell membrane is insufficient to elicit DivIVA targeting. 47 Nevertheless, this does not contradict our results: according to our model, what is important is that there be a difference in curvature: one part of the cell with low curvature, another part (the cell poles) with high curvature.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We should point out, however, that experiments in round cell mutants have indicated that simple curvature of the cell membrane is insufficient to elicit DivIVA targeting. 47 Nevertheless, this does not contradict our results: according to our model, what is important is that there be a difference in curvature: one part of the cell with low curvature, another part (the cell poles) with high curvature.…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, it has been shown that DivIVA localizes to division sites both in E. coli and, unexpectedly, in the fission yeast Schizosaccharomyces pombe. 47 However, this may again be due to binding to division apparatus proteins (possibly actin in S. pombe).…”
Section: Discussionmentioning
confidence: 99%
“…Also noteworthy are a number of hits, starting at rank 60 (UniProt:A4FLT9), which are annotated as putative homologues of DivI-VA, another bacterial cytoskeletal protein with predicted coiled coils (Edwards et al, 2000). We note that previously one DivIVArelated protein has been described as containing a hendecad motif (Bi et al, 2008).…”
Section: Results Of the Coiled Coil/fourier Transform/composition-basmentioning
confidence: 98%
“…Interestingly, one of these with similar domain organisation is DivIVA, another bacterial cytoskeletal protein that is essential for polarised growth in Actinomycetes (Flardh, 2003;Letek et al, 2008) whilst it controls cell division in others, such as Bacillus subtilis (Edwards et al, 2000;Edwards and Errington, 1997). It will be of great interest to establish to what extent Scy, FilP and DivIVA might share structural characteristics with potential relevance to their biological function.…”
Section: Discussionmentioning
confidence: 99%
“…25 It is worth mentioning that Errington and co-workers have shown that a protein targeting signal for division sites in conserved between prokaryotes and eukaryotes. 28 Hence, universal mechanisms for targeting both mRNAs and proteins are ancient and have apparently evolved in bacteria.…”
Section: Localization Of Bacterial Proteins Via Mrna Targetingmentioning
confidence: 99%